2017
DOI: 10.1039/c7tc00392g
|View full text |Cite
|
Sign up to set email alerts
|

UV-curable hybrid organic–inorganic composite inks with a high refractive index for printing interference images and holograms

Abstract: a Herein we report a new, facile and inexpensive methodology for obtaining highly refractive polymers suitable for inkjet printing using hexacoordinated titanium complexes (THC) and a UV-curable lacquer based on triethylene glycol dimethacrylate (TGD) that is a cheap and non-toxic monomer that can be rapidly polymerized under UV irradiation under ambient conditions. The resulting polymeric materials are characterized by a refractive index (RI) of about 1.85 in the solid state and have rheological properties su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Photopolymerizable compositions (PPCs) are widely used in photolithography [1][2][3][4][5][6][7][8] and jet printing [9][10][11][12][13][14][15] to form polymeric 2D-or 3D-structures. Besides the classical version of inhomogeneous photopolymerization of a PPC layer with a single source of light, [16][17][18][19] two-wavelength processes have recently been implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Photopolymerizable compositions (PPCs) are widely used in photolithography [1][2][3][4][5][6][7][8] and jet printing [9][10][11][12][13][14][15] to form polymeric 2D-or 3D-structures. Besides the classical version of inhomogeneous photopolymerization of a PPC layer with a single source of light, [16][17][18][19] two-wavelength processes have recently been implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric layers, which allow formation of inhomogeneous distribution of the refractive index, 1–4 are widely used to create elements of planar optics, 5,6,7 including flat light‐guides 8–10 . In modern radiation‐modified media (photoresists), it is possible to form nano‐ and micro‐sized structures with a complicated topology by photolithographic methods 11–14 .…”
Section: Introductionmentioning
confidence: 99%
“…The ability to micropattern polymeric materials with predesigned surface structures is of great significance in a wide range of applications including sensors, 1 , 2 tissue engineering, 3 6 lab-on-a-chip (LoC) devices, 7 and biofouling. 8 , 9 A large variety of micropatterning strategies have been developed based on soft lithography, 10 12 holography, 13 , 14 spatial light modulator (SLM), 15 inkjet printing, 16 19 direct laser interference patterning (DLIP), 20 25 and micro- and nanoprinting techniques. 26 28 Among these technologies, interference holography is a facile, inexpensive, and maskless technology to generate periodic structures in a photoresist layer.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to micropattern polymeric materials with predesigned surface structures is of great significance in a wide range of applications including sensors, , tissue engineering, lab-on-a-chip (LoC) devices, and biofouling. , A large variety of micropatterning strategies have been developed based on soft lithography, holography, , spatial light modulator (SLM), inkjet printing, direct laser interference patterning (DLIP), and micro- and nanoprinting techniques. Among these technologies, interference holography is a facile, inexpensive, and maskless technology to generate periodic structures in a photoresist layer. , Typically, a laser beam is split into two beams with identical linear polarizations from which an interference pattern is created with a pitch determined by the angle between two interfering laser beams . In the past, both negative and positive photoresist materials were employed extensively in interference holography to generate the microstructures in isotropic monomers and polymers and etching procedures are commonly employed to develop the surface relief structures. , For instance, Netti et al reported an effective and inexpensive technique to fabricate switchable holographic patterns in a light-sensitive azobenzene-based polymer which is used to guide cell adhesion and orientation.…”
Section: Introductionmentioning
confidence: 99%